Translatome and Transcriptome Profiling of Hypoxic-Induced Rat Cardiomyocytes - Zhijie Shen; Lixiong Zeng; Zhihui Zhang (Elsevier, 2020)
Adult cardiac hypoxia as a crucial pathogenesis factor can induce detrimental effects on cardiac injury and dysfunction. The global transcriptome and translatome reflecting the cellular response to hypoxia have not yet been extensively studied in myocardium. In this study, we conducted RNA sequencing (RNA-seq) and ribosome profiling technique (polyribo-seq) in rat heart tissues and H9C2 cells exposed to different periods of hypoxia stress in vivo and in vitro. The temporal gene-expression profiling displayed the distinction of transcriptome and translatome, which were mainly concentrated in cell apoptosis, autophagy, DNA repair, angiogenesis, vascular process, and cardiac cell proliferation and differentiation. A large number of genes such as GNAI3, SEPT4, FANCL, BNIP3, TBX3, ESR2, PTGS2, KLF4, and ADRB2, whose transcript and translation levels are closely correlated, were identified to own a common RNA motif "5'-GAAGCUGCC-3'" in 5' UTR. NCBP3 was further determined to recognize this RNA motif and facilitate translational process in myocardium under hypoxia stress. Taken together, our data show the close connection between alterations of transcriptome and translatome after hypoxia exposure, emphasizing the significance of translational regulation in related studies. The profiled molecular responses in current study may be valuable resources for advanced understanding of the mechanisms underlying hypoxia-induced effect on heart diseases.